2008
DOI: 10.1002/ajim.20579
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of occupational exposure limits

Abstract: Many older MAC values were either too high or not scientifically supported and therefore not health-based.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…4042 A more recent critical review found clear scientific deficiencies in the determination of TLVs. 43 As a case in point, nuclear specialists working with the nuclear fuel bundling process at GE, and elsewhere, have noted that despite the beryllium levels being kept below the limit, beryllium disease continues to be on the rise. 37…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4042 A more recent critical review found clear scientific deficiencies in the determination of TLVs. 43 As a case in point, nuclear specialists working with the nuclear fuel bundling process at GE, and elsewhere, have noted that despite the beryllium levels being kept below the limit, beryllium disease continues to be on the rise. 37…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] A more recent critical review found clear scientific deficiencies in the determination of TLVs. 43 As a case in point, nuclear specialists working with the nuclear fuel bundling process at GE, and elsewhere, have noted that despite the beryllium levels being kept below the limit, beryllium disease continues to be on the rise. 37 With its emphasis on air monitoring, the focus on exposure limits ignore perhaps the most reliable indication of overexposure reflected in the adverse health effect symptoms workers experience during exposures-whether the exposure is from direct handling or from bystander exposure.…”
Section: Limitation Of the Science For Assessing Work-related Diseasementioning
confidence: 99%
“…Since this paper, additional debate has occurred and the ACGIH continues to work to improve the process to help satisfy its critics. In Europe, the TLVs received considerable scrutiny in recent years, (213).…”
Section: Do the Tlvs Protect Enough Workers?mentioning
confidence: 99%
“…8−10 In accordance with the guidelines of the German Federal Institute for Occupational Safety and Health, the maximum concentration of hydrogen sulfide in the workplace is set at 5 ppm. 11,12 Therefore, a monitoring technique with real-time and high sensitivity/selectivity is crucial for the effective detection of H 2 S. Nickel oxide (NiO), as a representative p-type semiconductor material, boasts the advantages of low operating temperature and high catalytic activity, making it prominent in the realm of gas sensors. 13 Despite these merits, traditional single semiconductor gas sensors frequently grapple with challenges in meeting concurrent performance parameters such as high sensitivity, selectivity, and stability, and short response and recovery time, curtailing their potential in practical applications.…”
mentioning
confidence: 99%